Analyzing the Characteristics and Uniqueness of Tafsir Al-Ibriz by KH. Bisri Mustofa - Anjani I'anatul Maula; Azzurin Nisa' Salsabila Syafitri Inayah; Aris Fathur Rohman (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aim to explores the characteristics and uniqueness of Tafsir Al-Ibriz, authored by KH. Bisri Mustofa, a prominent figure in the Nahdlatul Ulama (NU) tradition. Tafsir Al-Ibriz stands out in the landscape of Quranic exegesis in Indonesia due to its distinctive approach and methodology. Employing a descriptive qualitative approach, this research delves into the interpretive methods, theological perspectives, and socio-cultural impacts of this tafsir. The findings indicate that Tafsir Al-Ibriz combines textual and contextual interpretation with a distinctive mystical and philosophical nuance, reflecting KH. Bisri Mustofa's unique perspective in understanding the messages of the Quran. Additionally, the tafsir demonstrates the influence of Sufi teachings in interpreting Quranic verses. Other unique characteristics of Tafsir Al-Ibriz include its emphasis on cultural preaching, particularly to the NU community, the use of Javanese language hierarchy known for its politeness (unggah-ungguh), the pesantren-specific style of translating Arabic texts, an objective interpretation of jihad devoid of political bias, adherence to the Shafi'i school of jurisprudence, and a mystical yet scientific approach. The theoretical implications of this research provide new insights into the diversity of interpretative approaches to the Quran in the Islamic world, highlighting the spiritual and philosophical dimensions presented by Tafsir Al-Ibriz. These findings also contribute to our understanding of the role of Sufism in the Islamic exegesis tradition and how theological thought can influence Quranic interpretation. This study aims to lay the groundwork for further research on classical and contemporary tafsir works, as well as deepen the relevance of Sufi thought in contemporary Quranic understanding. Contribution: This study reveals the uniqueness of Tafsir Al-Ibriz in its contextual approach, Sufism, and use of the Javanese language, enriching the study of Nusantara exegesis..